ANALYSIS OF AUDIT OPINION AND FINANCIAL RATIO (LIQUIDITY, SOLVENCY AND PROFITABILITY) ON PRICES SHARE WITH AUDIT DELAY AS MODERATE VARIABLES - Nurhasanah, Nurhasanah; Yunina, Yunina; Indrayani, Indrayani; Meldawati, Yesi; Bustami, Bustami (CV. Radja Publika, 2022)
This study aims to analyze the factors that influence stock prices in companies on the Indonesia Stock Exchange with audit delay as moderating. The population in this study amounted to 780 companies. The sampling method used purposive sampling. The independent variables used are audit opinion and financial ratios, namely the ratio of liquidity, solvency, profitability and audit delay as moderating variables. The sample was taken in 2020 as many as 64. The data was processed using Moderate Regression Analysis (MRA) cross section data which was processed with the E-Views application. The results of this study are expected to contribute to adding references to science and are expected to contribute to investors in making investment decisions.